2008
DOI: 10.1124/mol.108.048652
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ceramide Metabolism with a Potent and Specific Ceramide Kinase Inhibitor

Abstract: Ceramide kinase (CerK) produces the bioactive lipid ceramide-1-phosphate (C1P) and appears as a key enzyme for controlling ceramide levels. In this study, we discovered and characterized adamantane-1-carboxylic acid (2-benzoylamino-benzothiazol-6-yl)amide (NVP-231), a potent, specific, and reversible CerK inhibitor that competitively inhibits binding of ceramide to CerK. NVP-231 is active in the low nanomolar range on purified as well as cellular CerK and abrogates phosphorylation of ceramide, resulting in dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 29 publications
2
68
1
Order By: Relevance
“…This further illustrates the effects of CERK-derived C1P on eicosanoid production, and therefore implicates these mediators as players in the infl ammatory response. Of note, these fi ndings are partially in opposition to the reports by Bornancin and coworkers ( 23,24,49 ). Specifi cally, this group explored how cPLA 2 ␣ -dependent pathways were affected by the genetic ablation of CERK and this laboratory observed similar responses of cells derived from both wild-type and knockout animals to PMA/ionomycin treatment as well as the susceptibility of the whole animals to arthritis induction by both Ag and KRN serum.…”
Section: C1p Levels Are Not Affected In the Plasma Of Cerk ؊ / ؊ Micecontrasting
confidence: 52%
See 1 more Smart Citation
“…This further illustrates the effects of CERK-derived C1P on eicosanoid production, and therefore implicates these mediators as players in the infl ammatory response. Of note, these fi ndings are partially in opposition to the reports by Bornancin and coworkers ( 23,24,49 ). Specifi cally, this group explored how cPLA 2 ␣ -dependent pathways were affected by the genetic ablation of CERK and this laboratory observed similar responses of cells derived from both wild-type and knockout animals to PMA/ionomycin treatment as well as the susceptibility of the whole animals to arthritis induction by both Ag and KRN serum.…”
Section: C1p Levels Are Not Affected In the Plasma Of Cerk ؊ / ؊ Micecontrasting
confidence: 52%
“…This may be one alternative route to determining the role of a particular bioactive lipid in a particular biology to overcome compensatory mechanisms when targeting the biosynthetic pathways. As stated previously, there is still the question of the CERK inhibitor (NVP-231) developed by Novartis ( 49 ). Bornancin and coworkers reported that treatment of cells with this inhibitor had no effect on the stimulation of eicosanoid synthesis by various infl ammatory agonists ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression of hCERK increased the level of NBD-C1P accompanied with decreases in NBD-SM and NBD-GlcCer in CHO cells (Table 2). Similarly, Graf et al (14) reported that expression of CERK reduced levels of NBD-SM and NBD-GlcCer. Inhibition of NBD-GlcCer synthesis by PPMP in the present study and by tamoxifen (14) enhanced the formation of NBD-SM in CHO cells and in COS cells, respectively.…”
Section: Characteristics Of Nbd-ceramide Metabolism With or Without Nmentioning
confidence: 99%
“…Similarly, Graf et al (14) reported that expression of CERK reduced levels of NBD-SM and NBD-GlcCer. Inhibition of NBD-GlcCer synthesis by PPMP in the present study and by tamoxifen (14) enhanced the formation of NBD-SM in CHO cells and in COS cells, respectively. MAPPsensitive alkaline ceramidases such as ACER2 and ACER3 are localized to the Golgi apparatus (39,49).…”
Section: Characteristics Of Nbd-ceramide Metabolism With or Without Nmentioning
confidence: 99%
“…A specific inhibitor for CERK has already been developed [5], so we are focusing on the SMS2 inhibitor. We have already patented a screening method for discriminating between SMS1 and SMS2, which we expect to be helpful for identifying an SMS2-specific inhibitor.…”
Section: Are You Actually Working In This Direction?mentioning
confidence: 99%